The YouTube formula : how anyone can unlock the algorithm to drive views, build an audience, and grow revenue - Eves, Derral (John Wiley & Sons, Inc., 2021)
"This book will provide everything a YouTube creator needs to optimize their content strategy, including in-depth, applicable strategies for how to launch a channel, drive massive view and subscriber growth, build a brand and increase engagement, improve searchability, and drive commerce through YouTube. This book will explain things about YouTube's algorithms that haven't been taught in any other book about the platform, and it will be done in an easy-to-follow format. It will have case studies and real answers from creators and businesses who are getting the results that every YouTube creator wants. It will take readers through the successful content creation process and how to follow-through and follow-up for best results"--